Penerapan Pembelajaran Bebasis Media Mind Mapping Dalam Meningkatkan Kemampuan Berpikir Kreatif Siswa SMP - Eufrasia Jeramat; Marselina Lorensia; Maria Puspawati (UNIKA SANTU PAULUS RUTENG, 2020)
The study aims to know the application of of mind mapping in improving the mathematical creative thinking abilities of SMP Negeri 6 Langke Rembong students in academic year 2017/2018. The research is an experimental research using the desaign of Nonequivalent Control Group Design. The population of this research in all students of class VIII SMPN 6 Langke Rembong which amounted to 103 people divide into 3 classes with VIIIA 34 people, VIIIB 34 and VIIIC 34 people. Sampling is done by nonrandom class. The number of members of the study sample was 68 people. Data on creative thinking abilities were collected by descriptions test. Data were analyzed using t-test calculations with the polled formula variant. Based on the results of data analysis, it was found that the results t_count= 2,2921 and t_table= 1,9665 at significant level α=5% and degress of freedom=66. Because t_count > t_table then H_0 is rejected and H_1 is accepted, which means that mathematical creative thinking abilities of students is better than students mathematical creative thinking abilities using direct learning models in SPLDV